PERANAN IBNOE ABBAS DALAM MEMPERTAHANKAN KEMERDEKAAN INDONESIA DI INDRAGIRI 1945-1950 (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Ibnoe Abbas was Indonesian independence fighter figure fromCerenti. Freedom fighters are those who have fought against the invaders and defendedthe independence of Indonesia. While the purpose of this study is to know biography ofIbnoe Abbas, to know Ibnoe Abbas’s struggle, and then to know what he had done andstruggle after independence of Indonesia. The method used in this study is a historicalresearch method consisting of four stages, they are heuristics (source collection),source critic, interpretation, and historiography. Data obtained from the interviews plusthe data obtained from the book. The data obtained from interviews and the books wereanalyzed by using own words. The location of research conducted in Pekanbaru andKuantan Singingi regency, especially in Cerenti area. This research was carried outstarting from the issuance of research permit until this thesis finished. The technique ofcollecting data used are interview techniques, library research and documentationtechniques. The results showed that Ibnoe Abbas is a combatant against the colonistand has a role in maintaining the independence of the Republic of Indonesia. IbnoeAbbas's struggle was done by religious means. The struggle is done with guerrillatactics. Ibnoe Abbas's struggle was also done by political means by occupying severalimportant positions.Keywords: Ibnoe Abbas, Freedom Fighter, Guerilla.